Sodium arsenite does not affect prostate carcinogenesis in a chemically-hormonally-induced rat model. (30th May 2022) - Bosland, Maarten C.; Horton, Lori
Abstract: There is epidemiologic evidence to suggest that arsenic exposure is associated with risk of prostate cancer incidence and mortality. There are no studies indicating that arsenic can induce prostate cancer in animals. We evaluated whether drinking water exposure to sodium arsenite would affect prostate carcinogenesis in a rat model that depends on long-term low dose treatment with testosterone. WU rats received a sequential treatment with the antiandrogen flutamide followed by a single androgen administration to stimulate prostatic cell proliferation during which a single injection of N -methyl- N -nitrosourea was given. Two weeks later the animals received subcutaneous slow release testosterone-containing silastic tubing implants and provided with drinking water containing 5 mg/L sodium arsenite or with control drinking water for the duration of the 64 week-long experiment. Arsenite provided in drinking water did not modify the induction of prostate cancer in this rat model compared to control rats or survival. It also did not affect the growth of the animals or their drinking water intake. This animal study with drinking water exposure to 5 mg/L sodium arsenite does not support the notion that arsenic enhances prostate carcinogenesis.